Address by Royal Professor Ungku A Aziz at the Symposium on History and Philosophy, Draft 2 - Ungku Abdul Aziz, Ungku Abdul Hamid
This is an address given by Prof. Ungku Aziz at the symposium. After addressing the audiences, Ungku gave a brief story about Ibn Sina on his general work and contribution.